Development of calendar and planning production indicators based on the model of equipment life cycle - L. K. Sirotina (Омский научный вестник)
The article is devoted to the problem of substantiation and regulation of calendar and planned production indicators. Estimation of the equipment life cycle cost at the stage of investment in its acquisition and commissioning will make it possible to make decisions on the usefulness period, on the indicators of production capacity and the level achieved, on the permissible values of equipment downtime, the expediency of working on its maintenance and other indicators related to the use of production equipment.